2016
DOI: 10.1063/1.4949177
|View full text |Cite
|
Sign up to set email alerts
|

Concentrating solar power (CSP) power cycle improvements through application of advanced materials

Abstract: Abstract. Concentrating solar power (CSP) systems with thermal energy storage (TES) capability offer unique advantages to other renewable energy technologies in that solar radiation can be captured and stored for utilization when the sun is not shining. This makes the technology attractive as a dispatchable resource, and as such the Electric Power Research Institute (EPRI) has been engaged in research and development activities to understand and track the technology, identify key technical challenges, and enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…One of the major engineering barriers in the development of this category of these solar energy conversion systems is the maximum temperature at the receiver when directly exposed to air. The maximum operating temperature of the polycrystalline nickel-based alloys currently used in the design of industrial solar receivers is approximately 800 °C when 100,000 hours of use are considered [3]. In fact, previous investigations have revealed that Inconel 625 cannot withstand more than 36 h of exposure to air at 900 °C before oxide scale spallation occurs [4].…”
Section: Introductionmentioning
confidence: 99%
“…One of the major engineering barriers in the development of this category of these solar energy conversion systems is the maximum temperature at the receiver when directly exposed to air. The maximum operating temperature of the polycrystalline nickel-based alloys currently used in the design of industrial solar receivers is approximately 800 °C when 100,000 hours of use are considered [3]. In fact, previous investigations have revealed that Inconel 625 cannot withstand more than 36 h of exposure to air at 900 °C before oxide scale spallation occurs [4].…”
Section: Introductionmentioning
confidence: 99%
“…A disadvantage of using molten nitrates in thermal energy storage devices is their high corrosiveness towards metal piping and container walls [11,12]. Salt corrosion issues in long-term operation of about 30 years [12] currently necessitate the application of comparatively expensive Ni-base super alloys or austenitic stainless-steel grades [13]. For this reason, investment, and maintenance costs, involved in the usage of these high-price structural materials, are a major price driver and one of the main reasons for lacking competitiveness of CSP technology [14].…”
Section: Introductionmentioning
confidence: 99%
“…In power tower concentrating solar power systems (CSP), a large number of sun-tracking mirrors, known as heliostats, focus sunlight onto a receiver at the top of a tall tower. A heat-transfer fluid heated in the receiver is used to heat a working fluid, which, in turn, is used in a conventional turbine generator to produce electricity [1]. The challenge for a solar tower technology is related to ensuring the longevity of the receiver and demonstrating that the receiver material can handle high temperature fluxes across the 25-year lifespan of a plant.…”
Section: Introductionmentioning
confidence: 99%
“…Receivers working with air as the heat transfer fluid (HTF) can simplify the technology but the challenges, like absorber durability, receiver efficiency still remains to be solved. It can generally be said that for temperatures below 1073 K, nickel-based alloys with high chromium content are the most suitable for volumetric receivers due to their capacity to form oxides, which are black and highly absorbant [1]. The state-ofthe-art for solar absorbing materials used in solar towers, with air as HTF, is based on a commercially available black paint called Pyromark 2500s [3].…”
Section: Introductionmentioning
confidence: 99%